PERENCANAAN LANSKAP SUNGAI KELAYAN SEBAGAI UPAYA REVITALISASI SUNGAIDI KOTA BANJARMASIN KALIMANTAN SELATAN - Kukuh Widodo; Vera D Damayanti; Setia hadi (Jurnal Lanskap Indonesia, 2012)
Kelayan River is a small river in Banjarmasin City. Urbanization in the city has caused the physical development expansion up to the river bank and its impact has decreased the biophysical quality of the area. The objectives of this study are to identity landscape potencies and problems in Kelayan River area; to analize biophysical, social, cultural and economical aspect of Kelayan River which will influence the river landscape planning based  on biophysical aspect tosupport Kelayan River revitalization; which able to reflect waterfront city. Method of the study following the landscape planning process of Simonds (1983)consisted of preparation, collecting data, analysis, synthesis, and planning. This study uses biophysical approach modified from Astuti and Fandeli (2009). Biophysical aspects to be considered are rain fall, land coverage (Land Coverage Index IPL),  inundated area, land use (Land Use Suitability/KPL), vegetation and fauna. In analysis phase, the river is divided to seven segments based on administrative boundary. Each aspect will be analized quantitatively using scoring and weighting, as well as spatially. The analysis results biophysical quality classification i.e. very critical, critical, moderate, and good quality. The synthesis is directed to improve biophysical condition and to accommodate proposed land use through rehabilitation and conservation. The good biophysical quality segment is allocated to non-intensive rehabilitation zone, while the moderate biophysical quality segment is developed tosemi-intensive rehabilitation zone, and the critical and very critical segments are used for intensive rehabilitation zone and will be utilized for non-conservation area. Functional river with good quality of biophysical condition and reflecting waterfront city is the concept in the landscape plan for this area. The plan divides the area into three zones which are: (1) Non-intensive Rehabilitation Zone (16%), (2) Semi-intensive Rehabilitation Zone (33%), and Intensive Rehabilitation Zone (51%). The landscape plan is developed to spatial, circulation, vegetation, and settlement plans.